Monitoring tax revenues and tax reforms in EU Member States 2010. Tax policy after the crisis (Luxembourg, 2010)
"The report is prepared jointly by DG ECFIN and DG TAXUD of the European Commission. As the previous edition, the report analyses recent trends in tax revenues and tax reforms in EU Member States. A particular focus of this year's edition is onthe consequences of the global economic and financial crisis on revenue systems and the need to provide adequate policy responses. Given the size of the budgetary consolidation required after the crisis, a contribution from the revenue side will be necessary in many countries. The report analyses how revenue increases and tax systems in general could be designed in a growth-friendly way and to what extent some of the reforms would entail a need for coordination at the EU level. Moreover, it discusses tax policy issues related to the crisis and contributes to the ongoing discussion on financial sector taxation."